DETERMINAN KEPATUHAN PAJAK UMKM: LINGKUNGAN SEBAGAI VARIABEL MODERASI - Fransiska Isadora Sinaga; Amries Rusli Tanjung; Fajar Odiatma (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This research aims to examine the effect of tax information and modernization of the tax administration system on tax compliance to the entrepreneur of micro, small, medium entreprise in Pekanbaru city with environment as moderating variable. The data in this study is the primary data. The population in this study were all the Micro, Small, Medium Entreprises in the culinary industry in Pekanbaru City. The sampling method used in this study incidental method. The sample used in this study were 83 respondents. The method of data analysisused to test of hypothesis is SEM-PLS using WarpPLS 6.0 Version. The result of this study showed that tax information and modernization of the tax administration system had influence on the tax compliance. The environment could moderate the influence of tax information on tax compliance and the influence of modernization of the tax administration system on tax compliance